KARAKTERISTIK MEMBRAN KOMPOSIT BERBASIS KITOSAN/PVA TERMODIFIKASI LEMPUNG DARI BABAKAN MADANG BOGOR - Thria Kharisma; Nina Ariesta; Dian Arrisujaya (Universitas Nusa Bangsa, 2020)
The use of natural polymers as membranes of DMFC from chitosan was developed because it is more environmentally friendly and has high thermal stability, but the proton conductivity is low. The Clay from Babakan Madang, which contained of SiO2 50% was expected to increase proton conductivity and improve the characteristics of the polymer membrane. Chitosan / PVA based membrane synthesis was carried out by adding clay weight variations of 0.3, 0.6 and 0.9 g. The spectra of membranes investigated by FT-IR Â confirmed the presence of functional groups from chitosan/PVA/clay. Morphological analysis using SEM showed that there were granules of clay dispersed on the membrane. The determination of membran conductivity using EIS Â showed the highest proton conductivity value was a membrane with the addition of 0.6 g clay, it was 6.96 x 10-7 S / cm. The membrane water swelling produced on the three membranes tended to be high, with the smallest value of 56.69% on the membrane with the addition of 0.9 grams of clay. The methanol uptake data found that the conductivity of membrane with the addition of 0.6 grams of clay was 346.11%.